Migration and refuge: necessary topics for Nursing teaching in COVID-19 times - Denise Martin; Cássio Silveira; Lucimare Ferraz; Regina Yoshie Matsue (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to present an overview of migratory processes and access to health care for immigrants in Brazil and reflect on the importance of training in Nursing from an interdisciplinary perspective, focused on the care of this population in the context of a pandemic. Methods: this is a theoretical-reflective study based on the authors' experiences and anchored in the literature. Results: some particularities in the access to health services by migrants and refugees show how the pandemic's advancement and continuity impacted them in different ways. Interdisciplinary research and teaching are essential to study and better understand the health needs of the migrant population in Brazil, especially in the context of a pandemic. Final Considerations: the training of health professionals, especially in Nursing, must include these people's specificities so that future interventions are more sensitive and closer to their reality.